Community Economic Empowerment Training Based on Mosques through Productive Zakat Management in Banyuputih Village, Batang Regency - Akhmad Nurasikin; Tri Handayani; A Saiful Aziz; Ali Imron; Ubbadul Adzkiya; Aris Abdul Ghoni; Annisa Rahayu (Dimas: Jurnal Pemikiran Agama untuk Pemberdayaan, 2025)
Zakat management in mosques in Banyuputih is often still consumptive in nature and has not touched on aspects of sustainable economic empowerment. The purpose of this community service is to increase the capacity of mosque administrators in productive zakat management; provide entrepreneurship training to the community around the mosque and form a sustainable mosque-based economic empowerment model through collaboration between UPZ, the community, and universities. This training activity uses a participatory training approach through several training steps, namely: training, monitoring, and evaluation. Economic empowerment training based on the mosque through productive zakat management in Banyuputih Village has proven to have a significant impact on increasing the economic capacity of mustahik and strengthening the role of the mosque as a center for community empowerment. This model can be replicated in other mosques provided there is professional governance, continuous mentoring, and synergy between the mosque administrators, the community, and zakat institutions.